2020
DOI: 10.1055/s-0040-1713685
|View full text |Cite
|
Sign up to set email alerts
|

Health-Enabling Technologies for Telerehabilitation of the Shoulder: A Feasibility and User Acceptance Study

Abstract: Background After discharge from a rehabilitation center the continuation of therapy is necessary to secure already achieved healing progress and sustain (re-)integration into working life. To this end, home-based exercise programs are frequently prescribed. However, many patients do not perform their exercises as frequently as prescribed or even with incorrect movements. The telerehabilitation system AGT-Reha was developed to support patients with shoulder diseases during their home-based aftercare rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…In many cases, private spaces imply far more than ordinary living. For patients with chronic diseases or patients post-operationally discharged, their homes are places for not only living but also rehabilitation, and—in the future—could also facilitate medical diagnosis and therapy [ 2 , 3 , 4 ]. Health monitoring in private spaces will benefit the subjects who require assistance, such as the elderly, patients, and disabled persons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, private spaces imply far more than ordinary living. For patients with chronic diseases or patients post-operationally discharged, their homes are places for not only living but also rehabilitation, and—in the future—could also facilitate medical diagnosis and therapy [ 2 , 3 , 4 ]. Health monitoring in private spaces will benefit the subjects who require assistance, such as the elderly, patients, and disabled persons.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the following questions will be answered: (1) What types of sensors can be used for unobtrusive in-home health data acquisition? (2) Where should the sensors be placed? (3) Which data can be monitored in the smart home?…”
Section: Introductionmentioning
confidence: 99%
“…It has shown its technical feasibility and user acceptance of HETbased telerehabilitation in a pilot trial. 16 The aim of the described study in this publication is to show the efficacy of AGT-Reha compared with the current standard of care MET.…”
Section: Introductionmentioning
confidence: 99%
“…The prospective, single-arm, monocentric, explorative pilot study AGT-Reha-P2 showed the technical feasibility of AGT-Reha at patients' home. 16 AGT-Reha enables patients to exercise independently at home, while the corresponding data on exercise quality and quantity are automatically forwarded via a web interface to physical therapists. AGT-Reha-P2 also shows the general acceptance by treating physical therapists and patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation